sfcFC: uma abordagem de implementação de SFC em ambientes de nuvem com funções de rede utilizando Fastclick - Tavares, Renan Freire (2019)
The object of this research is the work of the Brazilian Sign Language translator and interpreter, as it aims to problematize some contradictions that permeate the constitution of the working class named translator and interpreter of Libras Portuguese within the educational context and stands for the following thesis: the work of the translator and interpreter of Libras-Portuguese is an immaterial work, which gives access to the cultural and historical assets of humanity and configures itself as a public service of basic rights. In the educational sphere it has been consolidated in a precarious way due to the aspects that are inscribed in a political economic conjuncture that is governed by the capitalist system, which leads the worker, which is the focus of this study, to unstable contracts and alienation. The theoretical-methodological framework on which this research is grounded is the historical-dialectical materialism, which is mobilized in order to understand the movement and the transformations of the object of study along the historical process of social organization in which it takes place as well as its contradictions. The focus is on the concept of work, taking it as a seminal category and conceiving it as a founding element of the social being. In this context, the dialogical theory of language and the historical-critical pedagogy also contribute to the process of social and historical understanding of the development of the work of the translator and interpreter of Libras-Portuguese and its implications in the transformative role of school education. The locus of this study is understood in two dimensions: a more comprehensive one, involving the federal sphere in the implementation of policies and the state education network of Espírito Santo, in where are implemented policies of hiring the workforce of the translator and interpreter of Libras-Portuguese, and another more specific one, which is located in the northern region of Espírito Santo, in which are evidenced the experiences of professionals who work there. As for the procedures to collect empirical material, there was: bibliographic research, documentary analysis and field research. The bibliographic research was conducted from searches in the Brazilian Digital Library of theses and dissertations. The documentary analysis focused on Decree No 5.626/2005; Law No 12.319/2010; the Brazilian Classification of Occupations (CBO) of 2010 and the public notices aimed at hiring translator and interpreter of Libras-Portuguese linked to the Secretariat of Education of the State of Espírito Santo, published between 2010 and 2018. The field research was conducted with translators and interpreters of Libras-Portuguese currently working within the educational context in the northern region of Espírito Santo, The contact with these workers was made through a training course aimed at those who in 2018 were hired for this job, or who had previously worked in this field. The process of analysis took place from the methodological nuance of the assumed theoretical reference, which expresses the dialectic that is established between the threefold Universal-Particular-Singular. Thus, this research highlights as a peculiarity investigated the object of this study itself, as the universality the capitalist mode of production, which is exposed by means of the political design that permeates the recognition of the work of the translator and interpreter of Libras-Portuguese and, as a singularity, situates the various conjunctures that permeate this occupation, more specifically, when it is circumscribed within the school space. The research addresses the work of the translator and interpreter of Libras in the educational sphere through the problematization of the work as a process and educational principle, pointing out the need to promote the development of class consciousness of this neophyte category of workers.